Full Endoscopic Decompression for Single Level Lumbar Stenosis: A Clinical Evaluation - Mohammad Nuruzzaman Khan; Shuvro Saha; Sabrina Shafiq; Avijit Dey; A M M Mukarrabin (Journal of Shaheed Suhrawardy Medical College, 2024)
Objective: This study aimed to evaluate the outcomes of full endoscopic decompression for single level lumbar spinal canal stenosis. Methods:This observational study was conducted on a total of 370 patients selected by purposive sampling from January 2022 and December 2023, presenting with symptoms more than 3 months and non-responding to conservative treatment. The procedure was performed by placing the patient on a radiolucent Wilson frame with single-shot epidural analgesia. Outcome was measured in terms of pain reduction using Visual analog scale (VAS) before and after surgery, at 3rd, 6th month, and functional outcome was assessed using the Modified MacNab criteria at 6th month, Results: The mean age of the patients was 56.1 years, with 63% male. The most common stenosis level was L4-L5 (36.5%). The mean operation duration was 53 minutes, and the postoperative complications were minimal. Significant improvement in pain levels was observed, with back pain reduced from a preoperative mean of 3.2 to 1.1 at six months, and leg pain from 7.2 to 1.0 (p < 0.001). According to the Modified MacNab criteria, 91.1% of patients reported excellent outcomes at six months, and 8.4% reported good outcomes. Conclusion: Full endoscopic decompression is a highly effective and safe method for treating lumbar spinal stenosis, providing substantial pain relief and excellent functional outcomes with minimal complications. J Shaheed Suhrawardy Med Coll 2023; 15(1): 3-7